Organizational Identification, Moral Identity Centrality and Organizational Engagement of Millennials: Moderating Impact of Psychological Entitlement - K. A. D. I. Udayangi; G. A. T. R. Perera (Colombo Business Journal)
This study analyses the moderating impact of psychological entitlement on the relationships between organisational identification, moral identity centrality and organisational engagement of Millennials. It addresses the knowledge gap pertaining to the organisational engagement of Millennials. Although engagement is conceptualised as a multidimensional construct, organisational engagement has only recently received the focus of attention of researchers. Despite Millennials being considered an entitled generation, psychological entitlement remains largely an unexplored area. The survey involved 285 Millennial Master of Business Administration (MBA) students in two leading universities in Sri Lanka. The data was analysed using Structural Equation Modeling. The results indicated no support for the premise that psychological entitlement moderated the relationships between organisational identification or moral identity centrality and organisational engagement of Millennials. The results provide valuable insights into the organisational engagement of Millennials and address some of the gaps in understanding the impact of psychological entitlement on organisational engagement.